2003
DOI: 10.1086/375224
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 8-Associated Hemophagocytic Lymphohistiocytosis in Human Immunodeficiency Virus-Infected Patients

Abstract: We retrospectively reviewed 5 cases of hemophagocytic lymphohistiocytosis (HL) associated with human herpesvirus 8 (HHV-8) reactivation in human immunodeficiency virus (HIV)-infected patients. All patients had clinical and biological features characteristic of HL. Pulmonary symptoms were present in all patients and were frequently life threatening. The mean number of HL episodes was 6. Four patients had HL-associated Kaposi sarcoma, and 3 had multicentric Castleman disease. The mean CD4 cell count was 200 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 29 publications
5
57
1
Order By: Relevance
“…The source of the HHV-8 infection is difficult to discern; however, since a small percentage of healthy American adults are HHV-8 seropositive, one possibility is transmission via a blood product while in the nursery. 15 Although HLH has been previously associated with HHV-8 infection, all of these reports have been in HIV-infected individuals with associated Kaposi sarcoma, [16][17][18] or patients who received a renal transplant. 19,20 Genetic analysis demonstrated that triplets A and B had the same compound heterozygous mutations in the perforin gene.…”
Section: Case Report Bmentioning
confidence: 99%
“…The source of the HHV-8 infection is difficult to discern; however, since a small percentage of healthy American adults are HHV-8 seropositive, one possibility is transmission via a blood product while in the nursery. 15 Although HLH has been previously associated with HHV-8 infection, all of these reports have been in HIV-infected individuals with associated Kaposi sarcoma, [16][17][18] or patients who received a renal transplant. 19,20 Genetic analysis demonstrated that triplets A and B had the same compound heterozygous mutations in the perforin gene.…”
Section: Case Report Bmentioning
confidence: 99%
“…However, the median CD4 + counts of the patients was significantly lower (200 cells/µl). [20] Case 1 was HIV-negative on ELISA and p24 antigen-negative at admission. Recent repeat HIV testing revealed that he is HIV-positive with a CD4 + count of 371 cells/µl and a VL of 104 copies/ml.…”
mentioning
confidence: 93%
“…Members of the herpesvirus family coincidentally are the most frequent triggers of viral-associated HLH. [5,6,20] These include Epstein-Barr virus (EBV), the reactivation of which has been implicated the most in viral-associated HLH, [21] CMV and human herpesvirus 8 (HHV-8). EBV was detected by in situ hybridisation of the trephine in case 2.…”
mentioning
confidence: 99%
“…26 Fardet et al reported Human Herpes virus 8 associated HLH among HIV-infected patients. 27 Malignancy associated acquired HLH (MAHS), with lymphoma being the commonest trigger, is well known entity in adults but rare in children. In a recent review of patients with lymphoma associated haemophagocytic syndrome (LAHS) in Japan showed that EBV genome was detected from more than 80% of T/NK cell lymphoma but rarely from B cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%